The novel mineralocorticoid receptor modulator balcinrenone protects against diet-induced cardiac microvascular dysfunction and plasma potassium elevation in mouse models - Matthew J. Wolf; Soumaya El Moghrabi; Roberto Palacios-Ramirez; Krister Bamberg; Leigh A. Bradley; Frederick H. Epstein; Judith Hartleib-Geschwindner; Frédéric Jaisser (PLoS ONE, 2026)
Overactivation of the mineralocorticoid receptor (MR) promotes tissue remodeling in patients with heart failure (HF) and/or chronic kidney disease (CKD). These patients may benefit from MR antagonists (MRAs); however, MRAs are underutilized, partly due to the risk of hyperkalemia. Balcinrenone is a novel, selective MR modulator that demonstrated renoprotection without an acute effect on urinary electrolyte excretion in preclinical studies, suggesting reduced hyperkalemia risk. Here, we present in vivo and in vitro studies comparing balcinrenone with eplerenone, an approved MRA. Myocardial perfusion reserve (MPR), an indicator of coronary microvascular remodeling, was evaluated in mice with diet-induced HF with preserved ejection fraction (HFpEF). MR target gene expression and markers of cardiac remodeling were evaluated using a clonal cell line of rat cardiomyocytes stably expressing MR (H9C2/MR+), and inflammatory and fibrotic processes were evaluated in primary human cardiac fibroblasts. Potassium (K + ) homeostasis was evaluated in mice with nephrectomy-induced CKD. In mice with diet-induced HFpEF, 30 mg/kg/day balcinrenone or 100 mg/kg/day eplerenone restored MPR to levels seen in mice without HFpEF. Balcinrenone and eplerenone inhibited aldosterone-induced expression of MR target genes and markers of cardiac remodeling in H9C2/MR+ cells, and excretion of collagen 1 and interleukin-6 in primary human cardiac fibroblasts, in a concentration-dependent manner. An overnight K + challenge in eplerenone-treated mice with nephrectomy-induced CKD yielded a higher plasma K + elevation than that observed in vehicle-treated CKD mice. By contrast, the plasma K + response in balcinrenone-treated mice with CKD was similar to what was observed in vehicle-treated CKD mice. Urinary K + excretion was not affected by balcinrenone or eplerenone treatment, but fecal K + excretion was elevated in CKD mice that were administered balcinrenone versus eplerenone. These results suggest that balcinrenone may be suitable for patients requiring additional cardiorenal protection through MR modulation but are at high risk of hyperkalemia.